Gd-nanoparticles functionalization with specific peptides for ß-amyloid plaques targeting. Issue 1 (December 2016) - Plissonneau, Marie; Pansieri, Jonathan; Heinrich-Balard, Laurence; Morfin, Jean-François; Stransky-Heilkron, Nathalie; Rivory, Pascaline; Mowat, Pierre; Dumoulin, Mireille; Cohen, Richard; Allémann, Éric; Tόth, Éva; Saraiva, Maria; et al.
Abstract Background Amyloidoses are characterized by the extracellular deposition of insoluble fibrillar proteinaceous aggregates highly organized into cross-β structure and referred to as amyloid fibrils. Nowadays, the diagnosis of these diseases remains tedious and involves multiple examinations while an early and accurate protein typing is crucial for the patients' treatment. Routinely used neuroimaging techniques such as magnetic resonance imaging (MRI) and positron emission tomography (PET) using Pittsburgh compound B, [11 C]PIB, provide structural information and allow to assess the amyloid burden, respectively, but cannot discriminate between different amyloid deposits. Therefore, the availability of efficient multimodal imaging nanoparticles targeting specific amyloid fibrils would provide a minimally-invasive imaging tool useful for amyloidoses typing and early diagnosis. In the present study, we have functionalized gadolinium-based MRI nanoparticles (AGuIX) with peptides highly specific for Aβ amyloid fibrils, LPFFD and KLVFF. The capacity of such nanoparticles grafted with peptide to discriminate among different amyloid proteins, was tested with Aβ(1–42) fibrils and with mutated-(V30M) transthyretin (TTR) fibrils. Results The results of surface plasmon resonance studies showed that both functionalized nanoparticles interact with Aβ(1–42) fibrils with equilibrium dissociation constant (Kd ) values of 403 and 350 µM respectively, whilst they did not interact with V30M-TTR fibrils. Similar experiments, performed with PIB, displayed an interaction both with Aβ(1–42) fibrils and V30M-TTR fibrils, with Kd values of 6 and 10 µM respectively, confirming this agent as a general amyloid fibril marker. Thereafter, the ability of functionalized nanoparticle to target and bind selectively Aβ aggregates was further investigated by immunohistochemistry on AD like-neuropathology brain tissue. Pictures clearly indicated that KLVFF-grafted or LPFFD-grafted to AGuIX nanoparticle recognized and bound the Aβ amyloid plaque localized in the mouse hippocampus. Conclusion These results constitute a first step for considering these functionalized nanoparticles as a valuable multimodal imaging tool to selectively discriminate and diagnose amyloidoses.